Ruthenium Hydride Catalyzed Direct Oxidation of Alcohols to Carboxylic Acids via Transfer Hydrogenation: Styrene Oxide as Oxygen Source - Barati, Behjat; Moghadam, Majid; Rahmati, Abbas; Tangestaninejad, Shahram; Mirkhani, Valiollah; Mohammadpoor-Baltork, Iraj (Synlett, 2013)
Direct oxidation of alcohols to carboxylic acids using styrene epoxide as oxidant in the presence of [RuHCl(CO)(PPh3)3] complex as catalyst is reported. By this catalytic system, a variety of primary alcohols including substituted benzyl alcohols as well as linear ones were directly converted into carboxylic acids in good to excellent yields.
Keywords: ruthenium hydride complex; alcohols; carboxylic acids; epoxides; oxidation